2016
DOI: 10.1038/srep32504
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-portable, wireless smartphone spectrometer for rapid, non-destructive testing of fruit ripeness

Abstract: We demonstrate a smartphone based spectrometer design that is standalone and supported on a wireless platform. The device is inherently low-cost and the power consumption is minimal making it portable to carry out a range of studies in the field. All essential components of the device like the light source, spectrometer, filters, microcontroller and wireless circuits have been assembled in a housing of dimensions 88 mm × 37 mm × 22 mm and the entire device weighs 48 g. The resolution of the spectrometer is 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(74 citation statements)
references
References 36 publications
1
71
0
2
Order By: Relevance
“…On image based analysis, Bayer filters in camera sensors have color overlaps, which would need to be removed to make measurements of specific light bands [19]. This means that in common cameras, RGB (Red, Green and Blue) channels represent broad and nonspecific sections of the light spectrum [20].…”
Section: Resultsmentioning
confidence: 99%
“…On image based analysis, Bayer filters in camera sensors have color overlaps, which would need to be removed to make measurements of specific light bands [19]. This means that in common cameras, RGB (Red, Green and Blue) channels represent broad and nonspecific sections of the light spectrum [20].…”
Section: Resultsmentioning
confidence: 99%
“…Reprinted from refs. (a), (b), (c), (d), (e), (f), (g), (h), and (i) with permission: CC‐BY 4.0 open access publication (a,g,i); Copyright 2015 and 2017, American Association for the Advancement of Science (b,c,d); Copyright 2001 and 2012, Royal Society of Chemistry (e,f); Copyright 2017, Springer Nature (h).…”
Section: Applications In Field Research and Diagnosticsmentioning
confidence: 99%
“…Fortunately, several portable spectrometers have become commercially available due to advancements in sensor and IT technology; e.g., startup companies such as Stratio, SCiO, and TellSpec have developed pocket-sized spectrometers [1][2][3]. Several research groups recently demonstrated that a low-cost smartphone spectrometer can be designed using off-the-shelf components [4][5][6].…”
Section: Introductionmentioning
confidence: 99%